2022
DOI: 10.1101/2022.11.14.516421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical reactivations predict future sensory responses

Abstract: SummaryPrevailing theories of offline memory consolidation posit that the pattern of neurons activated during a salient sensory experience will be faithfully reactivated, thereby stabilizing the entire pattern1-3. However, sensory-evoked patterns are not stable, but instead drift across repeated experiences4-7. To investigate potential roles of reactivations in the stabilization and/or drift of sensory representations, we imaged calcium activity of thousands of excitatory neurons in mouse lateral visual cortex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…One possibility by which "trial-based" frameworks of learning could be used to account for the data presented here is to assume that replays/reactivations of cue-reward experiences during the extended ITI provides "virtual trials" in lieu of the real trials experienced by mice 56,59 . While we cannot rule out this possibility, the similarity between the learning curves for the long and short ITI groups suggests that such a mechanism would somehow have to precisely replicate the effect of the missing 9/10 experiences in the long ITI group, and the available evidence suggests that neither the structure of replay/reactivation events nor the information they encode perfectly replicate past experiences [60][61][62][63][64][65][66] . We therefore suggest that our proposed non-trial-based learning rule is a more parsimonious explanation of the quantitative scaling observed here.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…One possibility by which "trial-based" frameworks of learning could be used to account for the data presented here is to assume that replays/reactivations of cue-reward experiences during the extended ITI provides "virtual trials" in lieu of the real trials experienced by mice 56,59 . While we cannot rule out this possibility, the similarity between the learning curves for the long and short ITI groups suggests that such a mechanism would somehow have to precisely replicate the effect of the missing 9/10 experiences in the long ITI group, and the available evidence suggests that neither the structure of replay/reactivation events nor the information they encode perfectly replicate past experiences [60][61][62][63][64][65][66] . We therefore suggest that our proposed non-trial-based learning rule is a more parsimonious explanation of the quantitative scaling observed here.…”
Section: Discussionmentioning
confidence: 87%
“…However, most demonstrations of the effectiveness of spaced versus massed cue-reward learning examine massed learning with a short ITI relative to the cue-reward delay 27,32 (ITI/trial ratio less than 10). Demonstrations like these do not rule out TDRL because under these conditions, extensions of TDRL that account for the ITI 37 can produce faster learning with longer ITIs (Extended Data Fig 1,60 s vs. 6 s). Thus, to rigorously examine the predictions of the dominant neurobiological "trial-based" models, experiments testing categorical, falsifiable predictions shared by TDRL implementations should be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, ( Deitch et al, 2021 ) reported a decrease in activity at the beginning of the experiment, which they suggested was correlated with some behavioral change, but we believe it could also be a result of the directed drift phase. ( Nguyen et al, 2022 ) also reported a slow directed change in representation long after familiarity with the stimuli. There is another consequence of the timescale separation.…”
Section: Discussionmentioning
confidence: 93%
“…Experimentally, [7] reported a decrease in activity at the beginning of the experiment, which they suggested was correlated with some behavioral change, but we believe it could also be a result of the directed drift phase. [40] also reported a slow directed change in representation long after familiarity with the stimuli. There is another consequence of the timescale separation.…”
Section: Discussionmentioning
confidence: 99%